Transformative Justice Through Social Engineering: Analyzing the Role of Legislation in Supporting the Rehabilitation of Drug Addicts to Become Productive Members of Society - Widoyoko, Wredha Danang; Ngaisah, Siti; Haryono, Haryono; Rahmawati, Diah Ayu; Sanusi, Ruchan (Westscience Press, 2024)
The research investigates law's role in promoting transformative justice through social engineering, focusing on rehabilitation and reintegration processes of drug addicts into society. This study applies a normative-juridical approach to evaluate Indonesia's legal frameworks for their effectiveness in handling addiction as a public health issue. Comparative analyses with international models, such as the decriminalization in Portugal and harm reduction policies in the Netherlands, show what a change of heart in legal philosophy might achieve. The findings put forward the majors lacuna in the present legislation: undue punitive, lack of supportive infrastructure, and stigma among society. Recommendations offered by the study go on to include legislative reform for rehabilitation, supportive infrastructure development, public-private partnership for effective reintegration. This paper advocates for a compassionate justice system that embeds transformative justice principles into legal frameworks, promoting societal productivity and inclusivity.